Non-dairy based desserts: a literature review (Research, Society and Development, 2020)
The Brazilian market for food products with low lactose content and foods for the vegan population, lactose intolerant and even the public that seeks lactose-free food by preference needs diversification. This review sought to describe articles that addressed the development and characterization of non-dairy based desserts. A search was made for references in the CAPES, Lilacs, Scielo, and ScienceDirect databases in September 2019 covering the period 2010-2020 and using the descriptive terms "Frozen desserts " or "Dairy alternatives " or "N on dairy "Or" Ice cream ". As selection criteria, research articles in English and Portuguese involving non-dairy desserts were used. The search allowed the identification of 5 articles that met the established criteria. Although the use of cow's milk substitutes has been explored by the dessert industry, there is still much to explore about the alternatives available to innovate in the design of non-dairy based desserts, so a review on the subject is extremely interesting.